Harnessing Blighia sapida as a Source of Novel Antimicrobials: Activity of Crude and Fractionated Extracts Against MDR Pathogens - Olumide Oluyele; Precious Temidayo Bimboye (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The rapid proliferation of multidrug-resistant pathogens has elevated antimicrobial resistance to a global crisis, necessitating the search for alternative antimicrobial sources. This study evaluated the antibacterial activity of crude and fractionated extracts of Blighia sapida against selected multidrug-resistant (MDR) clinical isolates. The crude extract was prepared by maceration and subsequently fractionated using solvents of varying polarity. Antibacterial activity was assessed through standard microbiological assays, and phytochemical constituents were profiled using high-performance liquid chromatography (HPLC). The crude extract exhibited broad-spectrum antibacterial activity, with inhibition zones increasing in a concentration-dependent manner. Escherichia coli was the most susceptible (20.0 mm at 100 mg/mL), followed by Klebsiella pneumoniae (17.0 mm), with minimum inhibitory concentrations (MICs) ranging from 25–50 mg/mL. Fractionation produced varied activities: the n-hexane fraction demonstrated minimal inhibition (?10 mm), the ethanolic fraction showed moderate activity against Enterococcus faecalis, Acinetobacter baumannii, and K. pneumoniae (5–10 mm), while the aqueous fraction was the most active, particularly against A. baumannii (11.0 mm) and E. coli (10.0 mm). Fraction MICs were higher (50–>100 mg/mL), indicating reduced potency compared to the crude extract. HPLC analysis identified kaempferol, gallic acid, chlorogenic acid, myricetin, quercetin, and caffeine as major constituents. These findings demonstrate that B. sapida possesses promising antimicrobial phytochemicals and highlight its potential as a valuable plant-based source for combating MDR bacteria.